Structure Development and Interfacial Interactions in High-Density Polyethylene/Hydroxyapatite (HDPE/HA) Composites Molded with Preferred Orientation - Sousa, R. A. (2002)
Composites of high-density polyethylene (HDPE) filled with sintered and nonsintered hydroxyapatite (HA) powders, designated as HAs and HAns, respectively, were compounded by twin screw extrusion. Compounds with neoalkoxy titanate or zirconate coupling agents were also produced to improve interfacial interaction and filler dispersion in the composites. The composites were molded into tensile test bars using (i) conventional injection molding and (ii) shear-controlled orientation in injection molding (SCORIM). This latter molding technique was used to deliberately induce a strong anisotropic character to the composites. The mechanical characterization included tensile testing and microhardness measurements. The morphology of the moldings was studied by both polarized light microscopy and scanning electron microscopy, and the structure developed was assessed by wide-angle X-ray diffraction. The reinforcing effect of HA particles was found to depend on the molding technique employed. The higher mechanical performance of SCORIMprocessed composites results from the much higher orientation of the matrix and, to a lesser extent, from the superior degree of filler dispersion compared with conventional moldings. The strong anisotropy of the SCORIM moldings is associated with a clear laminated morphology developed during shear application stage. The titanate and the zirconate coupling agents caused significant variations in the tensile test behavior, but their influence was strongly dependent on the molding technique employed. The application of shear associated with the use of coupling agents promotes the disruption of the HA agglomerates and improves mechanical performance.